Respuesta :

So to solve this question the first step should be to make 7 equal to 42. To do this multiply 7 by 6, likewise with x-4.
The new equation should be 42/6x-24 = 42/12. 
We now can just get rid of the numerators (top number) to get 6x-24=12.
The next step is to add 24 to both sides which would leave you with 6x=36.
Divide by 6 and the answer should be x=6
Cross multiply
7 * 12 = 42(x - 4)
Expand by using distributive property
84 = 42x - 168
42x = 84 + 168
42x = 252
    x = 6


ACCESS MORE